Community Behavior in Waste Management - Mulya, Adelse Prima; Witdiawati, Witdiawati; Hasan, Nur Bilqis Haibah Mufidah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Waste is an inseparable part of human life. Good community behavior in waste management can realize sustainable and environmentally friendly waste management. Conversely, in terms of health, waste that is not managed properly can facilitate the spread of disease so that the quality of public health can decrease. The design of this paper is a single case report. Data collection was carried out on February 15-20, 2024 in the population of Sukapura Village, Kiaracondong District, Bandung City with a total sampling technique of 1833 houses. The instrument used was the Self-Inspection Survey (SMD), with a validity and reliability value of 0.75. In general, the majority of houses already have waste disposal facilities. The behavior of the majority of residents of each house always disposes of garbage in its place, namely 91.43%. However, the habit of sorting waste still varies. The majority of residents of the house do not sort between organic and inorganic waste, namely 46.7%, while those who only sort are 32.79% and those who have sorted and processed it into compost or magot are 20.51%. One of the main problems in organic waste management in Kelurahan Sukapura is the low motivation of the community in general in the organic waste management process. For further research, it is necessary to examine more deeply and accountably related to the knowledge and perceptions of the people of Sukapura Village about waste and waste sorting, other factors that correlate with waste sorting behavior, and the reasons why the people of Sukapura Village do not sort waste so that work programs can be arranged that are targeted and sustainable.